Strategi Komunikasi Akun Instagram @Dlh_Jabar Melalui Konten Storytelling Untuk Menciptakan Interaksi Publik - Katliane Aprilian; Ahmad Taufiq Maulana Ramdan (CV. ITTC INDONESIA, 2026)
Government communication through social media is generally one-way, making it less than optimal in creating public interaction. To address this, the Instagram account @dlh_Jabar implemented storytelling content as a communication strategy in conveying environmental messages to the public. The implementation of this strategy showed an increase in audience reach and interaction compared to the period before storytelling was implemented, while inconsistencies in content production led to a decline in account performance. This study aims to analyze the communication strategy of the Instagram account @dlh_Jabar through storytelling content and examine the storytelling elements that play a role in creating public interaction. This study used a qualitative approach with a case study method through observation, in-depth interviews, and documentation. The results showed that the application of Storytelling as a communication strategy was able to create public interaction through Storytelling elements such as the contained message, conflicts that trigger audience involvement, characters that represent the community, and a relevant storyline.